1994
DOI: 10.1111/j.1365-2958.1994.tb00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of broadly pleiotropic phenotypes caused by an hfq insertion mutation in Escherichia coli K‐12

Abstract: The region immediately downstream from the miaA tRNA modification gene at 94.8 min contains the hfq gene and the hflA region, which are important in the bacteriophage Q beta and lambda life cycles. The roles of these genes in bacteria remain largely unknown. We report here the characterization of two chromosomal hfq insertion mutations. An omega (omega) cassette insertion near the end of hfq resulted in phenotypes only slightly different from the parent, although transcript mapping demonstrated that the insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
360
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(392 citation statements)
references
References 53 publications
28
360
0
3
Order By: Relevance
“…9 Our results with FtsZ showed that its expression in hfq -strains increased by ~15% in stationary phase (result not shown), which are in accordance with the result of Takada et al once the genetic background and growing conditions are taken into account. 8 This result suggested the involvement of at least one regulatory RNA.…”
supporting
confidence: 80%
“…9 Our results with FtsZ showed that its expression in hfq -strains increased by ~15% in stationary phase (result not shown), which are in accordance with the result of Takada et al once the genetic background and growing conditions are taken into account. 8 This result suggested the involvement of at least one regulatory RNA.…”
supporting
confidence: 80%
“…Inactivation of the hfq gene in diverse eubacteria caused pleiotropic physiological effects (32,33,46) and loss of virulence in pathogenic bacteria (9). However, no apparent phenotype emerged from an hfq knockout in Staphylococcus aureus (6).…”
mentioning
confidence: 99%
“…H fq is a pleiotropic posttranscriptional regulator that is a member of the Sm/Lsm superfamily and found in many Gram-negative and Gram-positive bacteria (1)(2)(3). Hfq binds to AU-rich stretches near stem loop structures of small noncoding RNAs (sRNA) and their target mRNAs to facilitate the annealing of their trans-encoded complementary sequences and hence to effect message-specific translational regulation (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%